Access to new medications for the treatment of drug-resistant tuberculosis: Patient, provider and community perspectives. (March 2015) - Lessem, Erica; Cox, Helen; Daniels, Colleen; Furin, Jennifer; McKenna, Lindsay; Mitnick, Carole D.; Mosidi, Thato; Reed, Caitlin; Seaworth, Barbara; Stillo, Jonathan; Tisile, Phumeza; von Delft, Dalene
Abstract: Multidrug-resistant tuberculosis (MDR-TB) is on the rise, and is difficult to treat. The approval of two new drugs, bedaquiline and delamanid, and growing evidence for the use of linezolid, offer renewed hope for addressing MDR-TB. However, access to these medicines remains a significant challenge. These drugs have not been registered for TB in most settings; barriers to preapproval access persist; and high pricing and intellectual property restrictions limit access. Many unanswered research questions about optimal use of these drugs also limit access, particularly for vulnerable populations. This review outlines challenges in accessing drugs encountered from the perspective of clinicians, patients and affected communities, and offers potential solutions.